HUBUNGAN MOTIVASI BELAJAR, EFIKASI DIRI DENGAN PEROLEHAN BELAJAR IPS PESERTA DIDIK MADRASAH IBTIDAIYAH DARUSSALAM - yarso, Bahtiar; Marzuki, Marzuki; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTop of FormThe research problem is "Is there a relationship between learning motivation and self efficacy with the acquisition of IPS learners of class VI in MIS Darussalam Sungai Kunyit"? Research variables consisted of independent variables (X1) learning motivation, self efficacy (X2) and dependent variables (Y) acquired Social Science (IPS). The purpose of this study was to describe the magnitude of the combined contribution of learning motivation, self efficacy, and learning achievement. The method used was quantitative descriptive method. with the Product Moment correlation statistical technique with the help of the SPSS 17 Program. The study was conducted in the Madrasah Ibtidaiyah Private Darussalam. The population is 12 learners. Technique of data collection: questionnaire and IPS value document. The results showed that self motivation and efficacy had correlation correlation (R) equal to 0,849 equal to 80% consisting of 49% study motivation and 31% self efficacy. This means that the combined contribution (together) of study motivation, the self-efficacy of the learners with the acquisition of IPS learners shows a significant relationship.Â Keywords : Learning achievement, Learning motivation, and Self-esteem Â